PENGARUH METODE PEMBELAJARAN KOOPERATIF DAN MINAT BELAJAR TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA - Kencanawaty, Gita (Universitas Indraprasta PGRI, 2016)
Abstract: The purpose of this study is to determine the effect of cooperative learning and the interest of learning the mathematics by students' critical thinking skills. The method used is an experimental method. A sample size of 60 students consisting of 30 students of experimental class and 30 studentsof control class, the sampling technique used is cluster sampling. The research instrument used is the test of preferential interest in learning (30 questions) and the ability to think critically shaped Mathematical descriptions, as many as 10 questions that tested the validity by the reliability coefficient of 0.884 and 0.707 Data were analyzed by using ANOVA two ways. The results showed: (1) There is a significant relationship between the method of learning on students 'critical thinking skills Mathematics of Fhitung = 111.647 and Sig = 0.000 <0.05, (2) There is a significant relationship between interest in learning to students' critical thinking skills Mathematics Fhitung = 4.619 and Sig = 0.036<0.05, (3) There is no significant interaction effect between learning and interest in learning the mathematics students' critical thinking skills of Fhitung = 3.207 and Sig = 0.079> 0.05. The results of this study are useful for the improvement of mathematics critical thinking skills in students by use of cooperative learning method, such as the pair of checks and think pair share classes in addition to the efforts encouragement to students to be more interested and liked math.Keywords: cooperative learning method, interest, critical thinking